Commuters’ Preferences and Willingness to Pay for Modern Public Utility Vehicle (MPUV) - Lalio, Ivy; Navarro, Gladys (Journal of Interdisciplinary Perspectives, 2024)
This study investigates commuters' preferences and predicts their Willingness to Pay (WTP) for Modern Public Utility Vehicles (MPUVs), focusing on comfort and convenience factors in an urban setting. A descriptive, quantitative approach was adopted, utilizing a tool-validated structured questionnaire based on the Contingent Valuation Method (CVM). Data were gathered from 324 respondents, consisting of senior high school students and teachers from two nearby private and public schools. Results indicate that while commuters' overall satisfaction with traditional PUVs was moderate, there was a dissatisfaction with environmental sustainability and safety features. Binary Logistic Regression (BLR) analysis identified personal and economic factors as positive predictors of commuters' willingness to pay for MPUVs, although these indicators were not statistically significant. However, two factors— the amount commuters were willing to pay and the overall importance placed on PUVs—showed a significant relationship with WTP. These indicators predict a positive change in the BLR model to answer —Yes, respondents are willing to pay for additional MPUVs. Also, it suggests that as the commuters find the commuter's comfort and convenience factors less important, their willingness to pay decreases. Thus, the findings suggest opportunities to enhance transportation infrastructure and services, recommending a shift toward a market-driven policy approach.